Be a Good Neighbor: Control Your Volunteer Wheat - Bowden, Robert L.; Brooks, H. Leroy; Peterson, Dallas E.; Shroyer, James P. (My University, 1991)
A publication about controlling volunteer wheat and how not controlling it can hurt you and your neighbors.
MF1004_1991-08
Keywords: MF1004; Crops; MF